Analisis User Experience Pada Website Sistem Informasi Tugas Akhir (SITA) Mahasiswa Menggunakan User Experience Questionnaire (UEQ) - Nugroho, Aristya Widya; Suprihadi, S (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The Final Assignment Information System (SITA) is one of the information systems owned by the Satya Wacana Christian University (SWCU) that was created to meet the needs of students to provide information related to their final project. The study was conducted to analyze the student user experience of the Final Project Information System (SITA) using the User Experience Questionnaire (UEQ). UEQ is a measurement method by reviewing the aspect of the user and the aspect of the user's comprehensive experience in using the information system with a questionnaire scale. The UEQ has 26 questions that require respondents to answer questions covering 6 aspects, including attractiveness, efficiency, clarity, accuracy, stimulation, and novelty. From the questionnaire obtained 39 student respondents who understand the use of the Final Project Information System (SITA). The test results got data on attractiveness, efficiency, accuracy, and stimulation got a positive evaluation. As for the clarity and novelty data received a normal evaluation. Then the results of the benchmark evaluation obtained attractiveness, clarity, accuracy, stimulation, and novelty to get a category below the average. For the results of the efficiency evaluation, the category is above the average.